Pembentukan Karakter Anak Usia Dini Berbasis Komunikasi Interpersonal Dengan Pendekatan Beyond Center of Circle Time: Pendampingan Kader Pos PAUD Desa Paciran Kabupaten Lamongan - Mazrikhatul Miah (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
One of the developmental tasks that must be completed in early childhood is language development. Often we meet early childhood develops biologically well but it has not developed well the development task. Language skills do not come just like that, but like other abilities, must be able to be grown and built so that it is in accordance with the appropriate stages of development. Communication between children and adults around them has a very significant role in the formation of children's character. Moral values ​​and general knowledge can only be well received by early childhood if delivered with appropriate communication. Openness, empathy and the richness of language and motivation of adults when playing with children is a requirement for effective interpersonal communication between the two. Effective communication produces effective learning outcomes as well. Not a few teachers and guardians of students who experience serious problems in communicating with early childhood because of lack of understanding of early childhood thinking and learning that affect the development of the language. This activity took place at POS PAUD Paciran Village, Lamongan Regency, where most of the population are fishermen families with an average level of education equivalent to junior and senior high school. The concrete experience gained by participants in this activity is to practice effective methods of communication in early childhood in learning experiences through play. With direct guidance and practice it is expected that participants can optimize their role as facilitators, motivators and evaluators for language development and other intelligence developments for early childhood.